2016
DOI: 10.1302/0301-620x.98b8.36400
|View full text |Cite
|
Sign up to set email alerts
|

Type C tibial pilon fractures

Abstract: This is currently the largest series reporting the outcome following fixation of complex AO type C tibial pilon fractures. Despite the severity of these injuries, we have demonstrated that a satisfactory outcome can be achieved in the appropriate patients using primary ORIF. Cite this article: Bone Joint J 2016;98-B:1106-11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 28 publications
4
47
5
Order By: Relevance
“…Considering these data, it is possible to compare our FAOS scores with results from other studies. Duckworth et al reported a mean FAOS score of 76 (mean follow-up 6 years) in complex tibial pilon fractures, compared with the score of 60.7 in our study (mean follow-up 41 months) [14]. Unfortunately, no subscores were reported in the tibial pilon fracture study.…”
Section: Discussioncontrasting
confidence: 78%
“…Considering these data, it is possible to compare our FAOS scores with results from other studies. Duckworth et al reported a mean FAOS score of 76 (mean follow-up 6 years) in complex tibial pilon fractures, compared with the score of 60.7 in our study (mean follow-up 41 months) [14]. Unfortunately, no subscores were reported in the tibial pilon fracture study.…”
Section: Discussioncontrasting
confidence: 78%
“…Considering these data, it is possible to compare our FAOS scores with results from other studies. Duckworth et al reported a mean FAOS score of 76 (mean follow-up 6 years) in complex tibial pilon fractures, compared with the score of 60.7 in our study (mean follow-up 41 months) [7]. Unfortunately, no subscores were reported in the tibial pilon fracture study.…”
Section: Discussioncontrasting
confidence: 78%
“…In a case series regarding classification schema, Gustilo et al described patients with ischemic limbs requiring emergency revascularization (type IIIC) as having the worst prognosis of all patients requiring limb salvage [6]. Traumatic ankle injuries are known to impact patient-reported function and quality of life [7,8]. However, little is known about patient-reported outcomes in people with severe injuries that require revisions and soft tissue reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Duckworth et al reported a mean FAOS score of 76 (mean follow-up 6 years) in complex tibial pilon fractures, compared with the score of 60.7 in our study (mean follow-up 41 months)[14]. Unfortunately, no subscores were reported in the tibial pilon fracture study.…”
contrasting
confidence: 78%